Transcranial Doppler to Predict Neurologic Outcome after Mild to Moderate Traumatic Brain Injury. (August 2016) - Bouzat, Pierre; Almeras, Luc; Manhes, Pauline; Sanders, Laurence; Levrat, Albrice; David, Jean-Stephane; Cinotti, Raphael; Chabanne, Russel; Gloaguen, Aurélie; Bobbia, Xavier; Thoret, Sophie; Oujamaa, Lydia; et al.
Abstract : Background: To assess the performance of transcranial Doppler (TCD) in predicting neurologic worsening after mild to moderate traumatic brain injury. Methods: The authors conducted a prospective observational study across 17 sites. TCD was performed upon admission in 356 patients (Glasgow Coma Score [GCS], 9 to 15) with mild lesions on cerebral computed tomography scan. Normal TCD was defined as a pulsatility index of less than 1.25 and diastolic blood flow velocity higher than 25 cm/s in the two middle cerebral arteries. The primary endpoint was secondary neurologic deterioration on day 7. Results: Twenty patients (6%) developed secondary neurologic deterioration within the first posttraumatic week. TCD thresholds had 80% sensitivity (95% CI, 56 to 94%) and 79% specificity (95% CI, 74 to 83%) to predict neurologic worsening. The negative predictive values and positive predictive values of TCD were 98% (95% CI, 96 to 100%) and 18% (95% CI, 11to 28%), respectively. In patients with minor traumatic brain injury (GCS, 14 to 15), the sensitivity and specificity of TCD were 91% (95% CI, 59 to 100%) and 80% (95% CI, 75 to 85%), respectively. The area under the receiver operating characteristic curve of a multivariate predictive model including age and GCS was significantly improved with the adjunction of TCD. Patients with abnormal TCD on admission (n = 86 patients) showed a more altered score for the disability rating scale on day 28 compared to those with normal TCD (n = 257 patients). Conclusions: TCD measurements upon admission may provide additional information about neurologic outcome after mild to moderate traumatic brain injury. This technique could be useful for in-hospital triage in this context. (Anesthesiology 2016; 125:346-54) Abstract : Transcranial Doppler parameters had excellent negative predictive value in that patients who did not undergo secondary neurologic deterioration were readily identifiable. Patients with abnormal transcranial Doppler patterns had greater disability 4 weeks injury. In combination with clinical examination and computed tomography scan, transcranial Doppler monitoring can inform clinicians about neurologic outcome in patients with mild to moderate traumatic brain injury.